Collective excitation of plasmonic hot-spots for enhanced hot charge carrier transfer in metal/semiconductor contacts1. Issue 18 (14th May 2015) - Piot, Adrien; Earl, Stuart K.; Ng, Charlene; Dligatch, Svetlana; Roberts, Ann; Davis, Timothy J.; Gómez, Daniel E.
<x xml:space="preserve">Abstract</x> Coherent interaction between Al nanodimers supported on TiO2 leads to enormous plasmonic enhancements in the photocatalytic decomposition of a small organic molecule.